The importance of social relationships: an analysis of the movie "Wonder" based on Vygotsky's learning theory (Research, Society and Development, 2023)
The development of a child is conditioned to several factors, among which, according to Vygotsky's Sociocultural Theory, says that social interactions comprise the basis for this development, directly influencing the construction of the individual as an autonomous subject. In this way, this work aimed to analyze the 2017 film “Extraordinário” from the perspective of Lev Vygotsky’s Sociocultural Theory, pointing out aspects and characteristics that directly affect the protagonist of the film. The methodology used then refers to a qualitative research, based on works by Lev Vygotsky and related studies. Auggie, who is a boy who is starting elementary school, finds himself facing the start of his social life. The challenge lies in the fact that Auggie has a genetic flaw that led to a facial deformation, making students and teachers look at him with distinction. Bringing to Vygostsky's theory, through the film it is possible to notice that there is a change in Auggie's entire school and family context. The development does not take place only for the protagonist, but for his surroundings. His parents learn to develop skills that allow Auggie to be more autonomous, since they are overprotective, in addition to learning to deal with their son's evolution. The suffering experienced by the protagonist due to issues such as bullying is another aspect that leads to mobilization on the part of teachers and staff and even other students, bringing a reflection on the relationships built in the environment.